Comparison of methods to identify individuals at increased risk of coronary disease from the general population. Issue 7404 (25th June 2003) - Wilson, S; Johnston, A; Robson, J; Poulter, N; Collier, D; Feder, G; Caulfield, M J
Abstract: Objectives To evaluate the guidelines on measurement of cholesterol in the national service framework for coronary heart disease and to compare alternative strategies for identifying people at high risk of coronary disease in the general population. Design Comparison of methods (national service framework criteria, Sheffield tables, age threshold of 50 years, estimated risk assessment using fixed cholesterol values) for identifying people with a 10 year coronary event risk of 15% or greater. Setting Health survey for England 1998. Subjects 6307 people aged between 30 and 74 years with no history of myocardial infarction, stroke, or angina. Main outcome measures Proportion of the total population selected for measurement of cholesterol and proportion of people at 15% or greater risk identified. Results The national service framework guidelines selected 43.4% (95% confidence interval 42.2% to 44.6%) of the study population for cholesterol measurement and identified 81.2% (80.2% to 82.2%) of those at 15% or greater risk. The Sheffield tables selected 73.1% (72.0% to 74.2%) for cholesterol measurement and identified 99.91% (99.83% to 99.99%) of those at 15% or greater risk. An age threshold of 50 years selected 46.3% (45.1% to 47.5%) for cholesterol measurement and identified 92.8% (92.1% to 93.4%) of those at 15% or greater risk. Estimated risk assessments using fixed cholesterol values selected 17.8% (16.8% to 18.7%) for cholesterol measurement and identified 75.9% (74.8% to 76.9%) of those at 15% or greater risk. Conclusion Measuring the cholesterol concentration of everyone aged 50 years and over is a simple and efficient method of identifying people at high risk of coronary disease in the general population.